ARTICLE FOR STRATEGIC ENVIRONMENTAL ASSESSMENT IN THE SECTORS OF (RENEWABLE) ENERGY, BIODIVERSITY AND CLIMATE CHANGE. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
As soon as possible Uzbekistan will also launch SEA-strategic environmental assessment like Canada, Australia and others. What is SEA and who or which governmental body conducts the SEA in term of efficiency and why we need SEA for Uzbekistan’s long term strategic plans and society prosperity. SEA is such a tool that leads to the sustainability while combining environmental dimension with socioeconomic dimensions. Also, it is long term and type of general impact assessment that takes into considerations of natural resources, ecosystem, biodiversity, renewable energy and etc.
Keywords: impact assessment, Policy, Plan, Program-PPP, SEA-Strategic environmental assessment, environmental and socioeconomic impacts, components, biodiversity, fossil fuels, renewable energy, climate change, ecosystem.